A felsőoktatás hallgatói rétegződésének térbeni megjelenése Budapesten - Ladányi, János (Tér és Társadalom, 1988)
An attempt is made in the present paper to highlight the spatial aspect of inequalities within the system of higher education. Analysing the way and proportions of spatial segregation among students of various universities and colleges can illustrate not only the inequalities within the system of higher education but can also provide useful contribution to knowledge on the segregation of various social groups in Budapest. The population of the survey: first year students at Budapest universities and colleges with a permanent residence in Budapest. (They, almost without exception, lived together with their parents in the same apartment.) 2,626 addresses were collected and were represented on a very detailed city map. The number of students of various universities and colleges ere aggragated by census planning tracts (amounting to some 500 in Budapest in 1980) and these data, together with the necessary additional information were analysed by computer: clusters were made on the basis of the social composition of the population by census tracts and it was found that the number of students related to the number of residents in the relevant age group was the highest in the most prestigious clusters and students were the most underrepresneted in areas with the lowest status. It could be also established that clustering in better positions within the system of higher education corresponds to segregation in favourable positions within the city structure. Analysing this isolation by indices of segregation or dissimilarity we concluded that the hierarchy generated by spatial segregation and the hierarchy produced by social distances actually coincide. The study could therefore point at a new aspect of the existing hierarchy within the Hungarian system of higher education and could highlight the characteristic feature of this hierarchy.